Is thickened hyaline cartilage on ultrasound a sign of osteoarthritis? A within-person, between-joint pilot study - Edoardo Cipolletta; Gianluca Smerilli; Riccardo Mirza Mashadi; Peter Mandl; Emilio Filippucci (BMC Rheumatology)
Abstract Objective To determine whether the presence of conventional radiography (CR)-detected osteophytes is associated with focal thickening of the hyaline cartilage by ultrasound (US) in the same area of the metacarpal head in a within-person, between-joint cross-sectional comparison in patients with hand osteoarthritis (HOA). Design 64 patients with HOA (classified using the 1990 ACR classification criteria) were screened. Participants were eligible for inclusion if they displayed osteophytes in at least one of their metacarpophalangeal (MCP) joints, no osteophytes in the contralateral corresponding MCP joint and no joint space narrowing (JSN) in either MCP joint by CR. In these patients, cartilage thickness was measured by US in 2 subregions of both metacarpal heads (i.e., the central force-bearing and the proximal peripheral area). Location-specific association between osteophytes and cartilage thickness was evaluated. Results 14/64 (21.9%) patients and 23 pairs of MCP joints were included in the analysis. Metacarpal heads with osteophytes had significantly thicker hyaline cartilage than contralateral ones without osteophytes in the proximal peripheral area of the hyaline cartilage [0.78 mm and 0.66 mm, respectively (p < 0.01)]. On the other hand, no difference in terms of cartilage thickness was found between the metacarpal heads with osteophytes and the contralateral ones without osteophytes in the central force-bearing area of the hyaline cartilage [0.65 mm and 0.66 mm, respectively (p = 0.53)]. Conclusions MCP joints with early radiographic HOA display thicker hyaline cartilage than contralateral MCP joints without radiographic signs of HOA, specifically in the proximal peripheral subregion of the metacarpal head.